2023
DOI: 10.1002/adma.202211027
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nanogenerator‐Integrated Metamaterial Concrete Systems for Smart Civil Infrastructure

Abstract: Creating multifunctional concrete materials with advanced functionalities and mechanical tunability is a critical step toward reimagining the traditional civil infrastructure systems. Here, the concept of nanogenerator‐integrated mechanical metamaterial concrete is presented to design lightweight and mechanically tunable concrete systems with energy harvesting and sensing functionalities. The proposed metamaterial concrete systems are created via integrating the mechanical metamaterial and nano‐energy‐harvesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The designed implant is capable to detect the post-surgery bone healing progress in a battery-free manner. Recently, Barri et al [67] implemented the meta-tribomaterials concept to develop novel concrete systems for smart civil infrastructure monitoring, as shown in Figure 3d. The developed smart concrete systems serve as sensing and energy harvesting systems to conduct continuous structural health monitoring.…”
Section: Metamaterial-enabled Autonomous Materials Systemsmentioning
confidence: 99%
“…The designed implant is capable to detect the post-surgery bone healing progress in a battery-free manner. Recently, Barri et al [67] implemented the meta-tribomaterials concept to develop novel concrete systems for smart civil infrastructure monitoring, as shown in Figure 3d. The developed smart concrete systems serve as sensing and energy harvesting systems to conduct continuous structural health monitoring.…”
Section: Metamaterial-enabled Autonomous Materials Systemsmentioning
confidence: 99%
“…The application of nanoparticles (NPs) in concrete and its potential benefits for improved strength and durability performance are well acknowledged. This stems from the fact that the application of supplementary cementitious materials (SCM) finer than cement and the resulting improvements in strength and durability increase with increasing fineness of SCM, which is attributed to packing density enhancement and reduction of calcium hydroxide (CH) content. The adoption of microsilica and subsequently nanosilica (SiNPs) has been attempted to exploit the benefits of improved packing density and pozzolanic reactivity of the material. In addition to SiNPs, a wide range of NPs including Al 2 O 3 , TiO 2 , Fe 2 O 3 , CaCO 3 , CuO, etc., have been explored to improve the mechanical, thermal, and electrical properties of cement systems. Of the above, SiNPs on account of their superior pozzolanic and microstructure properties have received wider attention from the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…An auxetic foam coated, concrete filled steel composite was tested numerically in [42] for effective damping of seismic waves to less than 10 Hz. Barri et al [43] have developed a conducive metamaterial concrete by filling it into 3D printed polymer auxetic lattices which performed well under cyclic compression load with an ability to conduct electricity for their application in smart civil infrastructure. Chen et al [44] studied the static and dynamic compressive behaviour of 3D printed auxetic lattice reinforced ultra-high-performance concrete (UHPC) and reported that auxetic lattices increased the energy absorption characteristics of UHPC with enhanced performance due to confining effect of lattices.…”
Section: Introductionmentioning
confidence: 99%